Medical devices in allergy practice - Popov, Todor A.; Passalacqua, Giovanni; González Díaz, Sandra Nora; Plavec, Davor; Braido, Fulvio; García Abujeta, Jose Luis; Dubuske, Lawrence M.; Rouadi, Philip W.; Morais Almeida, Mario; Bonini, Sergio; Cheng, Lei; Ansotegui, Ignacio J. (2020)
Medical devices provide people with some health benefits in terms of diagnosis, prevention, treatment, and monitoring of disease processes. Different medical specialties use varieties of medical devices more or less specific for them. Allergology is an interdisciplinary field of medical science and teaches that allergic reactions are of systemic nature but can express themselves at the level of different organs across the life cycle of an individual. Subsequently, medical devices used in allergology could be regarded as: 1) general, servicing the integral diagnostic and management principles and features of allergology, and 2) organ specific, which are shared by organ specific disciplines like pulmonology, otorhinolaryngology, dermatology, and others. The present position paper of the World Allergy Organization (WAO) is meant to be the first integral document providing structured information on medical devices in allergology used in daily routine but also needed for sophisticated diagnostic purposes and modern disease management. It is supposed to contribute to the transformation of the health care system into integrated care pathways for interrelated comorbidities.